Chasing the skip - Patterson, Janci (Henry Holt and Co., 2012)
When fifteen-year-old Rick's mother finally leaves for good, Ricki's absentee father steps in, taking Ricki with him as he chases bail "skips" across the country, but their fledgling relationship is tested as they pursue attractive, manipulative, seventeen-year-old Ian Burnham.